Host and Toxoplasma gondii genetic and non-genetic factors influencing the development of ocular toxoplasmosis: A systematic review (2016)
Toxoplasmosis is a cosmopolitan infection caused by the apicomplexan parasite Toxoplasma gondii. This infectious disease is widely distributed across the world where cats play an important role in its spread. The symptomatology caused by this parasite is diverse but the ocular affectation emerges as the most important clinical phenotype. Therefore, we conducted a systematic review of the current knowledge of ocular toxoplasmosis from the genetic diversity of the pathogen towards the treatment available for this infection. This review represents an update to the scientific community regarding the genetic diversity of the parasite, the genetic factors of the host, the molecular pathogenesis and its association with disease, the available diagnostic tools and the available treatment of patients undergoing ocular toxoplamosis. This review will be an update for the scientific community in order to encourage researchers to deploy cutting-edge investigation across this field. © 2016 Elsevier B.V.